Rendahnya Sikap Nasionalisme Mengakibatkan Meningkatnya Sikap Egoisme di Kalangan Remaja (Studi Kasus: Kelas VIII SMP N 35 Medan) - Imma Niani Handayani Gulo; Luruh Dwi Khinanti; Khairunnisa Manurung (Journal on Education, 2024)
Nationalism is a manifestation of people's love for the homeland and nationalism based on Pancasila will lead people to have an attitude of upholding human values and tolerance. Egoism is a behavior or action that is based on an impulse for self-interest. This study aims to identify how low nationalism attitudes result in increased selfishness among adolescents through a case study at UPT SMP N 35 Medan. This study uses qualitative descriptive methods using questionnaire data collection techniques, observation & documentation, this study aims to dig deeper into the causes of increasing egoism among adolescents and find out the relationship between nationalism and egoism. The number of respondents we used was 1 teacher and 20 grade VIII students of SMP N 35 Medan.